Insight into the mechanisms of biochar addition on pollutant removal enhancement and nitrous oxide emission reduction in subsurface flow constructed wetlands: Microbial community structure, functional genes and enzyme activity. (July 2020) - Liang, Yinkun; Wang, Qinghua; Huang, Lei; Liu, Maolin; Wang, Ning; Chen, Yucheng
Graphical abstract: Highlights: High pollutant removal and N2 O emission reduction were achieved in biochar CWs. Biochar addition enhanced microbial diversity and changed the community structure. Adding biochar increased functional microbe abundance related to nitrogen removal. High functional gene copies or enzyme activity were obtained in biochar CWs. Biochar addition is conducive to nitrogen transformation to moderate N2 O emission. Abstract: A set of constructed wetlands (CWs) under different biochar addition ratios (0%, 10%, 20%, and 30%) was established to analyze the pollutant removal performance enhancement and nitrous oxide (N2 O) emission reduction from various angles, including microbial community structure, functional genes and enzyme activity. Results revealed that the average removal efficiencies of ammonium (NH4 + -N) and total nitrogen (TN) were improved by 2.6%–5.2% and 2.5%–7.0%. Meanwhile, N2 O emissions were reduced by 56.0%–67.5% after biochar addition. Increased nitrogen removal efficiency and decreased N2 O emissions resulted from the increase of biochar addition ratio. Biochar addition changed the microbial community diversity and similarity. The relative abundance of functional microorganisms such as Nitrosomonas, Nitrospira, Thauera and Pseudomonas, increased due to biochar addition, which promoted the nitrogen cycle and N2 O emission reduction. High gene copy number and enzyme activity involved in nitrification and denitrification process were obtained in biochar CWs, moderating N2 O emission.